Validation of preoperative predictor score for difficult laparascopic cholecystectomy and a modified intraoperative grading score of the difficulty of laparascopic cholecystectomy: from a resource limited setting - Nurhussen Mossa Ahmed; Surafel Mulatu Djote; Getachew Desta Alemayehu; Wondwossen Amtataw; Sitotaw Mossa Ahmed (BMC Surgery)
Abstract Background Difficult laparascopic cholecystectomy has greater risk of biliary, vascular and visceral injuries. A tool to predict the difficulty help to prepare a head and avoid complications. Aim the aim of this study is validation of preoperative predictor score and a modified intraoperative grading score for difficulty of laparascopic cholecystectomy. Methods This study was a cross sectional, hospital based study on 200 patients. There are total of 10 scores for preoperative predictor score and 16 scores for the modified intraoperative grading of LC. Structured checklist questionnaire was used. Result prevalence of difficult LC was 40%. age greater than or equal to 50years, history of admission for acute cholecystitis, BMI > 30, palpable GB, impacted stone on imaging, adhesion burying GB, time to identify cystic artery/duct, bile/stone spillage and type of ligature were statistically significantly factors for difficult laparascopic cholecystectomy. Conclusion The preoperative scoring is statistically and clinically a good test for predicting the difficult level of laparascopic cholecystectomy (area under ROC = 0.948). The modified intraoperative measure of LC score is a statistically and clinically a good test for classifying the operative outcome of LC (area under ROC = 0.94).